S1PR3, as a Core Protein Related to Ischemic Stroke, is Involved in the Regulation of Blood–Brain Barrier Damage - Fan, Xuehui; Chen, Hongping; Xu, Chen; Wang, Yingju; Yin, Pengqi; Li, Meng; Tang, Zhanbin; Jiang, Fangchao; Wei, Wan; Song, Jihe; Li, Guozhong; Zhong, Di (Frontiers in Pharmacology, 2022)
Background: Ischaemic stroke is the most common stroke incident. Sphingosine1‐phosphate (S1P) receptor 3 (S1PR3) is a member of the downstream G protein-coupled receptor family of S1P. The effect of S1PR3 on ischaemic stroke remains elusive. Methods:We downloaded two middle cerebral artery occlusion (MCAO) microarray datasets from the Gene Expression Omnibus (GEO) database and screened differentially expressed genes (DEGs). Then, we performed weighted gene coexpression network analysis (WGCNA) and identified the core module genes related to ischaemic stroke. We constructed a protein–protein interaction (PPI) network for the core genes in which DEGs and WGCNA intersected. Finally, we discovered that S1PR3 was involved as the main member of the red proteome. Then, we explored the mechanism of S1PR3 in the mouse tMCAO model. The S1PR3-specific inhibitor CAY10444 was injected into the abdominal cavity of mice after cerebral ischaemia/reperfusion (I/R) injury, and changes in the expression of blood–brain barrier-related molecules were measured using PCR, western blotting, and immunofluorescence staining. Results: Both GEO datasets showed that S1PR3 was upregulated during cerebral I/R in mice. WGCNA revealed that the light yellow module had the strongest correlation with the occurrence of IS. We determined the overlap with DEGs, identified 146 core genes that are potentially related to IS, and constructed a PPI network. Finally, S1PR3 was found to be the main member of the red proteome.In the mouse cerebral I/R model, S1PR3 expression increased 24 hours after ischaemia. After the administration of CAY10444, brain oedema and neurological deficits in mice were ameliorated. CAY10444 rescued the decreased expression of the tight junction (TJ) proteins zonula occludens 1 (ZO1) and occludin after ischemia induced by transient MCAO (tMCAO) and reduced the increase in aquaporin 4 (AQP4) levels after tMCAO, preserving the integrity of the BBB. Finally, we found that S1PR3 is involved in regulating the mitogen-activated protein kinase (MAPK) and (phosphatidylinositol-3 kinase/serine-threonine kinase) PI3K-Akt signalling pathways Conclusions: In summary, S1PR3 and participates in the regulation of blood–brain barrier damage after cerebral I/R. S1PR3 is expected to be an indicator and predictor of cerebral ischaemia, and drugs targeting S1PR3 may also provide new ideas for clinical medications.